On the pea crabs found in the chiton Tonicia chilensis (Frembly, 1827) (Mollusca, Polyplacophora: Chitonidae) identified as “Orthotheres sp.” by Melzer & Schwabe (2008), and its reassignment to Calyptraeotheres Campos, 1990 (Crustacea: Pinnotheridae) - Campos, Ernesto (Zootaxa, 2018)
Crabs of the family Pinnotheridae have been considered a phylogenetically heterogeneous group and taxonomically problematic (Palacios-Theil 2009, 2016; Tsang et al. 2018). The lack of knowledge of sexual dimorphism and morphological variation throughout the life history for many species have complicated its taxonomy and has resulted in errors in its classification (Campos 1989, 1993, 2016). Consequently, if the taxonomy of these symbiotic crabs had been based on juveniles and undeveloped character states, the problems get even more serious (Campos 1989, 1993). Melzer & Schwabe (2008) studied three juvenile crabs living in the chiton Tonicia chilensis (Frembly, 1827) (Polyplacophora: Chitonidae) collected in Muelle Dichato, Chile, and they identified them as the putative invasive stage of a species of Orthotheres Sakai, 1969. The crabs are of the typical juvenile pinnotherid form with a masculine habitus, including a suborbicular carapace, large eyes and a slender pleon (= abdomen) with the telson well defined (Ocampo et al. 2017). Unpublished observations on juveniles and adults of several species of pinnotherid crabs by the author, for example, Juxtafabia muliniarum (Rathbun, 1918), Dissodactylus lockingtoni Glassell, 1935, D. xantusi Glassell, 1936, Calyptraeotheres granti (Glassell, 1933), Austinotheres angelicus (Lockington, 1877) and Tumidotheres margarita (Smith, 1870) have revealed that the third maxilliped exhibit little morphological variation through the post-larval stages of development (from juvenile to adult). This appendage, including the partial or total fusion of the ischium and merus (Fig. 1A–G; Fig 2A, C–G), has been considered a valuable feature for distinguishing genera in the family Pinnotheridae (Bürger 1895; Rathbun 1918; Manning 1993; Ahyong & Ng 2007; Campos 2009). According to Melzer & Schwabe (2008) the ischium and merus of the third maxilliped are completely fused, the carpus is larger than the propodus and the small dactylus is subterminally inserted on the propodus (Fig 1C), and as such the juveniles studied are possibly members of the genus Orthotheres Sakai, 1969. A detailed re-examination of the third maxilliped, chela of pereiopod 1 (cheliped) and pleon, however, has shown otherwise. Campos (1989) discussed the taxonomy of Orthotheres and treated all the species he recognised as belonging to this genus; characterising its members by its diagnostic third maxilliped palp structure. Ng & Ho (2014) rediagnosed the genus based on the type species, O. turboe Sakai, 1969, from Japan, and restricted it for three Indo-West Pacific species; commenting that the American species as well as some Indo-West Pacific taxa will need to referred to other genera when a full revision is done. This revision is now in progress by the author, PKL Ng and ST Ahyong. Until the revision is complete, the genus is treated here in the broader sense of Campos (1989) and Geiger & Martin (1999).